2005
DOI: 10.7202/705407ar
|View full text |Cite
|
Sign up to set email alerts
|

Distribution de Pseudomonas aeruginosa et Aeromonas hydrophila dans les eaux de la nappe phréatique superficielle en zone équatoriale au Cameroun et relations avec quelques paramètres chimiques du milieu.

Abstract: Une étude microbiologique et chimique a été menée pendant un an sur les eaux de sources et de puits de Yaoundé (Cameroun). Les analyses microbiologiques ont été faites suivant la technique des membranes filtrantes, et les analyses chimiques, suivant les techniques analytiques usuelles. Les abondances maximales mensuelles de Pseudomonas aeruginosa et de Aeromonas hydrophila varient respectivement de 1 à 22x103 UFC.100 ml-1 d'eau, et de 1 à 7,8x103 UFC.100 ml-1. Ces abondances bactériennes subissent d'amples flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Previous studies in this region also indicated the spatial and temporal fluctuations of the counts of P. aeruginosa and A. hydrophila in groundwater (Nola et al . ). The relative abundance of pathogenic E. coli identified varied from one water point to another (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies in this region also indicated the spatial and temporal fluctuations of the counts of P. aeruginosa and A. hydrophila in groundwater (Nola et al . ). The relative abundance of pathogenic E. coli identified varied from one water point to another (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Several studies have been carried out so far in the aquatic environments of Cameroon. The outcome of these studies is that surface and groundwater harbour faecal coliforms and opportunistic pathogenic bacteria like Pseudomonas aeruginosa and Aeromonas hydrophila, and the dynamics of their abundances, are affected by several hydrological and physicochemical environmental factors (Nola et al 2001;Djuikom et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Par ailleurs, la nappe phréatique M'nasra héberge de fortes densités en flore totale et en indicateurs de la contamination fécale, en accord avec ceux trouvées par Boutin et Dias [16] pour la nappe de Marrakech (Maroc). Les valeurs élevées en coliformes fécaux et streptocoques fécaux au niveau de la nappe phréatique M'nasra sont similaires à ceux trouvées au niveau de la nappe phréatique de Yaoundé (Cameroun) où les concentrations maximales annuelles fluctuent de 2 à 3,5 log 10 /100mL pour les coliformes fécaux et de 1,9 à 3,7 log 10 /100 mL pour les streptocoques fécaux [17]. De même des fortes concentrations en coliformes fécaux sont enregistrées au niveau des eaux de puits de la nappe phréatique de Yembeul au Sénégal avec des fluctuations entre 0 et 6,8 log 10 /100 mL [18].…”
Section: Discussionunclassified
“…Most studies have indicated the pollution of this underground water resource by faecal bacteria such as Escherichia coli and Streptococcus feacalis, and by opportunistic bacteria such as Aeromonas hydrophila and Pseudomonas aeruginosa, distribution of bacteria being impacted by some chemical factors [14,15]. The presence of such organisms is indicative of the existence of pathogenic bacteria such as Salmonella typhi and Vibrio cholerae which can cause health hazards.…”
Section: Introductionmentioning
confidence: 99%